Analisis Efektivitas Katalis Fe/Zeolit pada Cracking Minyak Jelantah dalam Pembuatan Biofuel - Lisa Adhani; Reni Masrida; Nicky Putri Angela; Ridwan Rendi Nugroho (PendIPA Journal of Science Education, 2020)
Petroleum fuels are increasingly limited in resources making the theme of sustainable energy one of the top issues in the world. Supported by increasing awareness of clean and sustainable environments. Biofuel derived from vegetable oil is a renewable energy that has the potential to be developed in Indonesia, given that Indonesia is rich in biodiversity. Used cooking oil is used cooking oil produced from vegetable oil which has the potential to produce biofuels. Used cooking oil is non-edible and can even be said to be waste, so its use as a fuel does not compete with food oil and has a calorific value that is almost the same as conventional fuel. The process of catalytic cracking of used cooking oil has been carried out in this research. The cracking process is carried out using a Zeolite catalyst that has been impregnated with Fe. Catalytic Cracking is carried out on a distillation flask with catalyst variations, catalyst size and temperature as independent variables. Fe / Zeolite catalyst variations are 1%, 3%, 5%, and 7%, with sizes 60, 80 and 100 mesh, while the temperature variations are 250oC and 350oC. Whereas the dependent variable is time, which is 2 hours. The optimum results obtained with the greatest yield on the use of catalysts with a catalyst concentration of 3%, catalyst size of 60 mesh and a temperature of 350oC. The physical test carried out was a specific gravity test that was equal to 0.8241 at the optimum yield with a catalyst concentration of 3%, and 1.0392 on the use of a catalyst with a concentration of 5%. From the results of the GCMS test shows that the component that dominates the biofuel produced is gasoline seen from the C6 compound content of 17.2% and C8 of 13.7%. It can be said that the largest amount is biogasoline shown by the presence of C5-C11 compounds of 72.4% than biodiesel indicated by the percentage of C12-C15 of 24.1%